Changes in depression and anxiety through mindfulness group therapy in Japan: the role of mindfulness and self-compassion as possible mediators - Toru Takahashi; Fukiko Sugiyama; Tomoki Kikai; Issaku Kawashima; Siqing Guan; Mana Oguchi; Taro Uchida; Hiroaki Kumano (BioPsychoSocial Medicine, 2019)
Abstract Background Mindfulness-based interventions are increasingly being implemented worldwide for problems with depression and anxiety, and they have shown evidence of efficacy. However, few studies have examined the effects of a mindfulness-based group therapy based on standard programs for depression and anxiety until follow-up in Japan. This study addresses that gap. Furthermore, this study explored the mechanisms of action, focusing on mindfulness, mind wandering, self-compassion, and the behavioral inhibition and behavioral activation systems (BIS/BAS) as possible mediators. Methods We examined 16 people who suffered from depression and/or anxiety in an 8-week mindfulness group therapy. Measurements were conducted using questionnaires on depression and trait-anxiety (outcome variables), mindfulness, mind wandering, self-compassion, and the BIS/BAS (process variables) at pre- and post-intervention and 2-month follow-up. Changes in the outcome and process variables were tested, and the correlations among the changes in those variables were explored. Results Depression and anxiety decreased significantly, with moderate to large effect sizes, from pre- to post-intervention and follow-up. In process variables, the observing and nonreactivity facets of mindfulness significantly increased from pre- to post-intervention and follow-up. The nonjudging facet of mindfulness and self-compassion significantly increased from pre-intervention to follow-up. Other facets of mindfulness, mind wandering, and the BIS/BAS did not significantly change. Improvements in some facets of mindfulness and self-compassion and reductions in BIS were significantly correlated with decreases in depression and anxiety. Conclusions An 8-week mindfulness group therapy program may be effective for people suffering from depression and anxiety in Japan. Mindfulness and self-compassion may be important mediators of the effects of the mindfulness group therapy. Future studies should confirm these findings by using a control group. Trial registration University Hospital Medical Information Network (UMIN CTR) UMIN000022966. Registered July 1, 2016, https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000026425